The expression profiling and clinical significance of a chronic pain-related gene IL1R1: IL1R1 Gene Expression and Chronic Pain Clinical Significance - Zhou, Ling; Wu, Chenglong; Li, Rongchun; Wang, Li; Han, Dongji (Cellular and Molecular Biology, 2023)
Chronic pain is a disease that existed during cancer treatment for a long time. It has been reported that interleukin (IL)-1 is involved in the inflammatory response during tumor development. IL1R1 and IL1R2 are members of the IL-1 receptor family of cytokine receptors. However, few studies have reported the role of chronic pain-related genes, IL1R1, in pan-cancer. In this study, 8 lumbar disc prolapse (LDP) patients and 8 controls with differentially expressed genes were investigated to find chronic pain-related genes. Then, IL1R1 was analyzed using the TCGA database. The clinical survival data from TCGA were used to analyze the prognostic value of IL1R1. This study further evaluated the relationship between IL1R1 and immune checkpoints, immune-activating genes, immunosuppressive genes, chemokines, and chemokine receptors. IL1R1 was expressed in varying degrees in most TCGA tumor types, indicating a better survival status. The expression of IL1R1 is closely related to T cell infiltration, immune checkpoints, immune-activating genes, immunosuppressive genes, chemokines, and chemokine receptors. The results show that IL1R1 is a kind of potential cancer biomarker. Coordination with other immune checkpoints IL1R1k may adjust the immune microenvironment, immunotherapy can be applied to the development of new targeted drugs.